Dynamic interplay between antagonistic pathways controlling the σ(32) level in Escherichia coli - Morita, Miyo T. (The National Academy of Sciences, 2000)
The heat-shock response in Escherichia coli depends primarily on the transient increase in the cellular level of heat-shock sigma factor σ(32) encoded by the rpoH gene, which results from both enhanced synthesis and transient stabilization of normally unstable σ(32). Heat-induced synthesis of σ(32) was previously shown to occur at the translation level by melting the mRNA secondary structure formed within the 5′ coding sequence of rpoH including the translation initiation region. The subsequent decrease in the σ(32) level during the adaptation phase has been thought to involve both shutoff of synthesis (translation) and destabilization of σ(32)-mediated by the DnaK–DnaJ chaperones, although direct evidence for translational repression was lacking. We now show that the heat-induced synthesis of σ(32) does not shut off at the translation level by using a reporter system involving translational coupling. Furthermore, the apparent shutoff was not observed when the synthesis rate was determined by a very short pulse labeling (15 s). Examination of σ(32) stability at 10 min after shift from 30 to 42°C revealed more extreme instability (t(1/2)=20 s) than had previously been thought. Thus, the dynamic change in σ(32) stability during the heat-shock response largely accounts for the apparent shutoff of σ(32) synthesis observed with a longer pulse. These results suggest a mechanism for maintaining the intricate balance between the antagonistic pathways: the rpoH translation as determined primarily by ambient temperature and the turnover of σ(32) as modulated by the chaperone (and presumably protease)-mediated autogenous control.